JOB SATISFACTION: DETERMINANTS AND ITS IMPLICATIONS IN HUMAN RESOURCE MANAGEMENT - Ernanda, Yovie; Ritonga, Ricky Rafii; Simbolon, Safii (Universitas Dharmawangsa, 2025)
Job satisfaction is a fundamental concept in Human Resource Management (HRM) that profoundly impacts employee behavior, organizational productivity, and overall performance. It reflects employees’ emotional and psychological attitudes toward their job, influenced by various intrinsic and extrinsic factors. This article aims to comprehensively explore the determinants of job satisfaction, its relationship with individual and organizational performance, and effective strategies to enhance it. Intrinsic factors, such as the meaningfulness of tasks, recognition, and opportunities for professional growth, significantly contribute to positive job satisfaction. Additionally, extrinsic factors like competitive compensation, a supportive work environment, and harmonious interpersonal relationships further strengthen employees' attachment and commitment to their roles. The analysis highlights how job satisfaction drives higher productivity, reduces absenteeism, and minimizes turnover rates. Conversely, dissatisfaction can lead to disengagement, increased stress, and higher operational costs due to frequent employee replacements.To address these challenges, the article proposes several strategies, including fostering open communication, implementing robust career development programs, offering fair rewards and recognition, and ensuring work-life balance through flexible work policies. By adopting these approaches, organizations can cultivate a motivated and loyal workforce, thereby enhancing long-term sustainability and competitiveness.